The Effect of Competency, Organizational Commitment, Work Environment, and Motivation on Employee Productivity - Tetti Sartika Samosir; Pras Rendi; Nunung Ayu Sofiyati (GoAcademica Research & Publishing, 2026)
The purpose of this research is to examine the connection between productivity and competence, organizational commitment, and the work environment, and to determine how work motivation moderates this relationship. A quantitative explanatory technique was used to conduct the study at PT XYZ in Bengkulu. With the use of purposive sample and proportionate stratification by division and work shift, 168 out of 287 operational personnel were chosen to participate in the survey. PLS-SEM using SmartPLS 4 was used to evaluate data received from a structured questionnaire that used a Likert scale. There is no statistically significant relationship between factor (X1), factor (X2), or factor (X3) and productivity, according to the data. In contrast, there is a positive and statistically significant relationship between intrinsic drive at work and output. Furthermore, the correlation between factor (X1) and productivity is moderated by factor (Z), as is the correlation between factor (X3) and productivity. This means that when employees are highly motivated, a good factor (X3) and competent workers are more likely to result in increased productivity. On the other hand, the correlation between factor (X2) and productivity is unmodified by job motivation. A total of 26.7% of the variation in productivity across workers is explained by the model. In the context of car production, these results emphasize the importance of intrinsic motivation in maximizing the impact of both human and environmental factors on productivity.